2019
DOI: 10.7717/peerj.7095
|View full text |Cite
|
Sign up to set email alerts
|

Age-related kinematic performance should be considered during fast head-neck rotation target task in individuals aged from 8 to 85 years old

Abstract: Kinematic behavior during fast cervical rotations is a useful parameter for assessing sensorimotor control performances in neck-pain patients. However, the influence of age in asymptomatic individuals from children to older people still needs to be explored. Our aim was to assess the impact of age on sensorimotor control performance of the head-neck with execution time and kinematic variables (time of task, mean speed/acceleration/deceleration, overshoots (OSs), minimum/maximum speed) during standardized fast … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 46 publications
(78 reference statements)
2
14
0
Order By: Relevance
“…Various noninvasive three-dimensional motion capture systems are used in the field of cervical research in order to evaluate kinematic variables going beyond simple range of motion such as speed, acceleration and deceleration using electrogoniometers [16], ultrasound waves [17], optical-based systems [18,19] and inertial sensors [20] and so on. Nevertheless, their dimension, complexity, and cost make such systems often difficult to use in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Various noninvasive three-dimensional motion capture systems are used in the field of cervical research in order to evaluate kinematic variables going beyond simple range of motion such as speed, acceleration and deceleration using electrogoniometers [16], ultrasound waves [17], optical-based systems [18,19] and inertial sensors [20] and so on. Nevertheless, their dimension, complexity, and cost make such systems often difficult to use in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…No signi cant kinematic differences were observed between the healthy control group compared to the normative data of Hage et al [23] .…”
Section: Resultsmentioning
confidence: 50%
“…Indeed, we showed that patients were slower to become as accurate (no signi cant difference in overshoots) as healthy controls. Moreover, our results show that the overshoot variable analysis is obviously representative of neck sensorimotor status quality and ts with the speed accuracy trade-off in the neutral zone [19,23].…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations